1. ESTIMASI JUMLAH ANAK YANG LAHIR BERDASARKAN PEMERIKSAAN ULTRASONOGRAFI TRANSCUTANEUS PADA KAMBING KACANG (Capra Sp.) (Estimation of Foetal Number in Kacang Goat (Capra Sp.) Base on Transcutaneus Ultrasonography) - Megi Satria; Tongku N Siregar; Arman Sayuti; Juli Melia; Hamdan Hamdan; Rosmaidar Rosmaidar; Abdul Harris (Jurnal Medika Veterinaria, 2016)
This research aims to know the accuracy of transcutaneus ultrasonography (USG) to determine number of kacang goat (Capra sp.) foetal. The animals used in this research were 6 goats aged of 1.5-2.5 years old, have a normal estrus cycle and mated naturally. The inspection was conducted after 53 to 97 days of pregnancy. The results showed that two goats were diagnosed as positive single pregnant (one foetus), and the others (four goats) were diagnosed as positive multiple pregnant (two foetus). Two goats were diagnosed single pregnant confirmed at delivered time in which all goats gave birth to one goat. All of the goats diagnosed positive multiple pregnant were gave birth to two goats. The accuracy of using transcutaneus USG to determine the number of single foetus and twins are 100%.Key words: ultrasonography, transcutaneus, accuracy, kacang goat, foetus